RELATIONSHIP BETWEEN GROWTH OF NITRARIA SCHOBERI AND SOME SOIL PROPERTIES - A. Mojiri; A. Jalalian (Journal of Animal and Plant Sciences, 2011)
A study was carried out to investigate the relationship between growth of Nitraria schoberi and some soil properties in Segzi plain in the eastern of Isfahan province (center of Iran). Due to its special geographic condition, Iran is a dry and semidry zone of the world. Nitraria schoberiis a drought-resistant shrub plants. In the study area, Nitraria schoberiplants were all of similar age. A total of 6 profiles were studied and from each profile depth (0-30, 30-60 and 60-90 cm), sampling was conducted. For each soil sample obtained, electrical conductivity (EC), sodium ions (Na), bicarbonate (HCO3-) and the percentage of gypsum, calcium carbonate and clay were measured. Plant physiological parameters including plant height and top were measured. The data thus obtained were analysed through the SPSS software. The results indicated that the electrical conductivity, sodium ions, HCO3- and the percentage of clay had negative effects on plant physiologic parameters whilst the percentage of calcium carbonate had a positive effect on plant physiologic parameters. However, the percentage of gypsum did not have any significant effect on the plant physiologic parameters.
Keywords: Desert; physiologic parameters; Nitraria schoberi; Sodium; Soil.